2014
DOI: 10.3892/ol.2014.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fascin upregulation in primary head and neck squamous cell carcinoma is associated with lymphatic metastasis

Abstract: Fascin is an actin-bundling protein that is associated with cellular motility and cancer-cell invasion. The present study aimed to examine the expression of fascin in head and neck squamous cell carcinoma (HNSCC) and its potential use as a biomarker. In a prospective study with a median follow-up time of 48.8 months, tumor tissues, adjacent healthy tissues and cervical lymph node metastases were collected from 25 patients and analyzed by immunohistochemistry. The specimens were scored according to the intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In this regard, numerous studies reported that the Fascin gene plays an important role in the progression of several human carcinomas including CRC. [13][14][15] Moreover, earlier investigations demonstrated that Fascin expression is correlated with poor prognosis in human CRC. [16][17][18] Indeed, Fascin is an actin-binding protein that is expressed in a large number of human carcinomas and is usually upregulated in cancer cells specially during epithelial to mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous studies reported that the Fascin gene plays an important role in the progression of several human carcinomas including CRC. [13][14][15] Moreover, earlier investigations demonstrated that Fascin expression is correlated with poor prognosis in human CRC. [16][17][18] Indeed, Fascin is an actin-binding protein that is expressed in a large number of human carcinomas and is usually upregulated in cancer cells specially during epithelial to mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%
“…(13) They also did not find fascin expression in the well-differentiated keratin-pearl-containing cases of OSCC. Moreover, unlike Chen and Alam (7,9) , other researchers (10,12) did not find a relationship between grade, microscopic stage, and fascin expression; however, they found that a relationship was established when lymph nodes were involved. The possible reasons for the disparity of results might be technical errors and the different steps of performing IHC staining, visual counting, using the computer, and the sample size examined.…”
Section: Discussionmentioning
confidence: 85%
“…These results are consistent with the results of many other studies conducted on fascin expression and its relationship with gender, age, and tumor location. (7,9,10,11,12) Similarly, Chen et al (9) did not find fascin expression intensity to have a relationship with age, gender, and tumor location and fascin expression percentage to have a relationship with the patients' age and gender. Although the majority of buccal mucosa samples expressed less than 55% fascin, the tongue samples of OSCC mostly expressed more than 55% fascin, which was statistically significant.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations